Integrating Suitable Planting Time and Bio-rational Pesticides to Suppress the Pest Complex of Soybean in Northeast India - Firake, D. M.; Behere, G. T.; Baiswar, P. (Indian Journal of Hill Farming, 2018)
A series of experiments was conducted to identify the suitable planting time and ecofriendly approaches to minimize the pest damage in soybean during 2012-2014. The experiments were conducted in randomized block design and each treatment wasreplicated thrice. Stem fly (Ophiomyia phaseoli) damage was significantly reduced in seed treatment with imidachloprid as well as in foliar spraying with imidachloprid and also when soybean crop planted after the end of June. Population of blister beetles (Mylabris spp.) was almost nil in soybean planted in mid July. Foliar spraying of Beauveria bassiana and N.S.K.E. 5% two times during flowering was very effective against foliage and flower feeding insects. On the basis of prior experiments, three pest management modules were formulated and evaluated for yield potential. Overall results indicate that, the soybean seeds may best be planted during mid July and the soybean crop could be sprayed alternatively with N.S.K.E and B. bassiana during flowering to suppress the damage caused by major pests of soybean. Foliar spray of imidachlorpid may be given only if thestem fly damage exceeds economic threshold level.